Intensity Ratio of Kβ/Kα in Selected Elements from Mg to Cu, and the Chemical Effects of Cr Kα1,2 Diagram Lines and Cr Kβ/Kα Intensity Ratio in Cr Compounds - Ito, Yoshiaki (2023)
Y. Ito acknowledges the financial support for the measurements of a part of the data by the REXDAB Collaboration that was initiated within the International Fundamental Parameter Initiative. This research was supported in part by FCT (Portugal) under research center grants UID/FIS/04559/2020 (LIBPhys). This work was also supported by the National Science Centre, Poland under grant number 2017/25/B/ST2/00901 and grant number 2021/05/X/ST2/01664, and by the Slovenian Research Agency (P1-0112). A. Kahoul and A. Hamidani acknowledge the support of the DGRSDT, Ministry of Higher Education and Scientific Research, Algeria, and of Mohamed El Bachir El Ibrahimi University, under project (PRFU) No. B00L02UN340120220001. Paul Indelicato is a member of the Allianz Program of the Helmholtz Association, contract n° EMMI HA-216 “Extremes of Density and Temperature: Cosmic Matter in the Laboratory”. P.I. acknowledge support from the PESSOA Hubert Curien Program 2022, Number 47863UE. Publisher Copyright: © 2023 by the authors.